Compétence(s) interculturelle(s) et culture de l’Autre dans l’enseignement-apprentissage du texte littéraire au secondaire - TIFOUR Thameur (My University, 2016)
Literature is the language of thought, the secret of art, the soul of revelation and the mirror of people. It is featured by different artistic creations stemmed from aesthetic value and its semiotic multi-dimensionality. It gives life to words with a sense of effects generated from reading. This research proposes an analysis of literary text of an intercultural category in FFL class. It is hypothesized that the exploitation of the literary language in class may revalues its institutional status, which is involved in rewriting the objectives recommended by the noosphere on the exploration of potential and gives meaning to intercultural communication.
Keywords: literary text, literariness, intercultural, communicability, representation.